Sustainability assessment of smallholder farms in developing countries. Issue 5 (28th May 2017) - Goswami, Rupak; Saha, Subhrajit; Dasgupta, Purnabha
ABSTRACT: Smallholder farms in developing countries are key to global food security and sustainability of agricultural systems. Suitable tools are needed to assess the utility of these systems for long-term policy interventions. We outline the development of a sustainability index for smallholder systems by amalgamating ecological frameworks and sustainable livelihood framework. We critically describe the process involved in the development of the indicator framework, selection of indicators, their measurement and assignment of weight, and aggregation to arrive at a composite index. A practical tool based on this index may prove helpful for long-term sustainability assessment in smallholder farms of developing countries.